The effect of dexmedetomidine on postoperative behaviour change in children: a randomised controlled trial. (13th June 2020) - Lee‐Archer, P. F.; von Ungern‐Sternberg, B. S.; Reade, M.; Betts, M.; Haenke, D.; Keys, A.; Rance, T.; Gibbons, K.; Long, D.
Summary: Children may develop changes in their behaviour following general anaesthesia. Some examples of negative behaviour include temper tantrums and nightmares, as well as sleep and eating disorders. The aim of this study was to determine whether dexmedetomidine reduces the incidence of negative behaviour change after anaesthesia for day case surgery in children aged two to seven years. Children were randomly allocated to one of three groups: a premedication group received 2 μg.kg -1 intranasal dexmedetomidine; an intra‐operative group received 1 μg.kg -1 intravenous dexmedetomidine; and a control group. The primary outcome was the incidence of negative behaviour on postoperative day 3 using the Post‐Hospitalisation Behaviour Questionnaire for Ambulatory Surgery (PHBQ‐AS) and the Strength and Difficulties Questionnaire (SDQ). Secondary outcomes included: the incidence of negative behaviour on postoperative days 14 and 28; anxiety at induction; emergence delirium; pain; length of recovery and hospital stay; and any adverse events. The data for 247 patients were analysed. Negative behaviour change on postoperative day 3 was similar between all three groups when measured with the PHBQ‐AS (47%, 44% and 51% respectively; adjusted p=0.99) and the SDQ (median scores 7.5, 6.0 and 8.0 respectively; adjusted p=0.99). The incidence of negative behaviour in the group who received dexmedetomidine intra‐operatively was less at postoperative day 28 (15% compared with 36% in the dexmedetomidine premedication group and 41% in the control group, p<0.001). We conclude that dexmedetomidine does not reduce the incidence of negative behaviour on postoperative day 3 in two to seven‐year olds having day case procedures. [Correction added 15 January 2021, after first online publication: In original published version, there was a dosage error in the Summary section, which specified mg instead of μg; this version corrects the error]. 요약: 소아들은 마취 후 행동에 변화가 생길 수 있다. 몇몇 부정적 인 행동의 예는 수면장애, 섭식장애, 잦은 투정과 악몽을 포함 한다. 본 연구의 목적은 2‐7세 소아에서 통원 수술 마취 후에 덱스메데토미딘이 부정적인 행동 변화 발생을 감소시키는지 여부를 판단하는 것이었다. 소아들은 세 그룹 중 하나에 무작 위로 배정되었다: 사전투약그룹, 2 mg.kg‐1 덱스메데토미딘 비 강내 투여; 수술 중 그룹, 1 mg.kg‐1 덱스메데토미딘 정맥내 투여; 대조군. 1차 결과는 수술 후 3일 차에 Post‐Hospitalisation Behaviour Questionnaire for Ambulatory Surgery (PHBQ‐AS)와 Strength and Difficulties Questionnaire (SDQ)를 사용한 부정적인 행동의 발생이었다. 2차 결과는 다 음을 포함한다: 수술 후 14일과 28일의 부정적 행동 발생, 마 취 유도시 불안, 각성시섬망, 통증, 회복 기간 및 병원 체재 기 간, 모든 부작용. 247명 환자의 데이터를 분석하였다. PHBQ‐AS(각각 47%, 44%, 51%, 보정 p = 0.99)와 SDQ(각각 중위수 7.5, 6.0, 8.0, adjusted p = 0.99)로 측정하였을 때 수술 후 3일 차에 나타난 부정적인 행동 변화는 세 그룹 모두에서 유 사하였다. 수술 중 덱스메테토미딘을 받은 그룹의 부정적 행 동 발생률이 수술 후 28일(덱스메테토미딘 사전투약 그룹의 36%와 대조군 그룹의 41%와 비교하였을 때 15%, p ＜ 0.001) 에 낮았다. 저자들은 덱스메테토미딘이 통원 수술을 받은 2‐7 세 소아에서 수술 후 3일에 부정적 행동의 발생을 감소시키지 않는다고 결론짓는다.